Perspektif Amanah dalam Al-Qur’an - Muhammad Irham Ghifari; Adha Saputra; Taufik CH (ZAD Al-Mufassirin, 2020)
In the Qur'an Allah Subhanahu Wa Ta'ala also teaches us many things, including worship, muamalah, and behaving like a Muslim, one of which is being trustworthy like our Prophet Muhammad Shallallah 'Alaihi Wasallam, he is known as an honest merchant, trustworthy, and responsible, not only among Muslims but also among the Quraish disbelievers, the Prophet was known as a trustworthy person, the important lesson we can take here is that the Prophet Muhammad Shallallah 'Alaihi Wasallam was on his way to be a prophet and apostle, he built and trained this trait in muamalah or trade, as we know that one way if we want to see a person's trustworthy attitude then muamalah in money matters with him, this paper discusses the verses that become our foundation in studying the perspective of Amanah in the Qur'an.